Place of Agronomy in Soil Conservation - Singh, R M (Journal of Soil and Water Conservation, 2022)
Soil erosion started inunediately after the prehistoric man opened the first furrmv for the production of some type of vegetation for his consumption. It has been going on ever since, Wherever man has bared the land to devastating action of rain and wind. With increase in human population, area under cultivation increased to limited fulfil their pressing needs. With limited knowledge of agriculture people destroyed the natural vegetation and continued to grow crops on clean cultivated area. Erosion developed simultaneously at a faster rate with development in agriculture. This has resulted in rendering most cultivated area into ravines and uncontrollable waste. It is very recently that the people of modern age have begun to realize the dangerous effects of devastating evil — soil erosion. They have realized the importance of soil protec- tion against its losses and a term, more scientifically and technically, known as Soil Conservation has been applied to it.